PENGARUH INDEKS KAPASITAS FISKAL (IKF) DAN INDEKS RUANG FISKAL (IRF) TERHADAP DANA PERIMBANGAN TAHUN 2015-2020 PADA 122 KABUPATEN DAERAH TERTINGGAL DI INDONESIA - Slamet Widodo (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2020)
Underdeveloped regions are characterized as regions with unavailability of natural resources which causes high financial dependence to the central government in the form of balance funds transfer. This causes the low level of autonomy of underdeveloped regions because of the lack of local revenue sources. The average Fiscal Capacity Index (IKF) of underdeveloped regions during 2015-2018 was 0,75 or in the moderate category. Some underdeveloped regions in Papua and West Papua have high IKF because of the Special Autonomy fund. In terms of fiscal space (IRF), the freedom of underdeveloped regions in determining their own spending priorities by 36% throughout 2016-2018. One of the main goals of fiscal decentralization is to eliminate horizontal gaps between regions, which in turn must be reflected in the budgeting process where regions that are more in need (underdeveloped regions) will get more allocations than other better-off regions.The purpose of this study is to analyze the influence of IKF and IRF on the balance of funds for the 2015-2018 period in 122 underdeveloped regions in Indonesia. The data used are data on balancing funds, IKF, IRF for the period 2015-2018 sourced from BPS, the Ministry of Finance, and other relevant agencies. The analysis tool uses Panel Data regression with the Fixed Effect Model. The results of the analysis show that the IKF variable has a significant positive effect on the balance fund and the IRF variable has a significant negative effect on the balance fund.